Studi Literatur: Pengembangan Bahan Ajar Bahasa yang Menarik untuk Anak Sekolah Dasar dengan Menggunakan Worksheet Interaktif - Zahara, Dini Putri; Pateka, Philsa Arin; Arvita, Tihan; Kuntarto, Eko (Asian Journal of Early Childhood and Elementary Education, 2024)
Language learning at the elementary school level requires an approach that is able to attract students' interest, while building basic language skills that are effective and meaningful. One innovative approach in the digital era is the use of interactive worksheets, which offer a dynamic and adaptive learning experience. This article aims to examine several studies related to the development of interactive worksheet-based language teaching materials aimed at increasing student motivation, participation and in-depth understanding. The method used is a literature study, which includes collection, analysis and synthesis of various relevant research regarding the effectiveness of interactive worksheets in increasing student engagement in the elementary school environment. The results of the literature review show that interactive worksheets can provide several significant benefits, including supporting various student learning styles, stimulating language exploration, and encouraging critical thinking skills. In addition, the findings show that interactive worksheets provide flexibility for teachers in adapting learning materials to students' needs and interests. The main challenges in implementing interactive worksheets include the need for adequate technological facilities and increasing teacher competence in designing interactive and effective teaching materials.